Avaliação de populações de azevém anual quanto à tolerância ao alumínio tóxico e estimativa de tamanho de amostra para estudos de diversidade genética com marcadores AFLP - Bresolin, Adriana Pires Soares (2007)
Italian ryegrass (Lolium multiflorum Lam.) is the most important forage grass in Rio Grande do Sul, as well as in most part of temperate and subtropical regions of the world. Due to its importance, in 1999 Embrapa Temperate Agriculture initiated activities to develop an Italian ryegrass breeding program, which started with collecting germplasm in Southern Brazil. However, collecting and conservation of germplasm, without its characterization, results in genebanks as simple repositories of genetic materials, without use. To established correct strategies of efficient management and use of genebanks, is extremely important to know the amount and quality of genetic resources available in genebanks. This study was developed aiming to evaluate Italian ryegrass populations to aluminum tolerance and to establish the optimum bulk size to estimate genetic diversity among populations with AFLP markers. Two experiments were undertaken; the first one evaluated six Italian ryegrass populations in hydroponic solution to aluminum (Al3+) tolerance. The results showed that the nutrition solution combined with the different aluminum doses (0; 7 and 21 mg.L-1) were efficient to discriminate the populations evaluated, showing the presence of genetic variability among populations. Tolerance to Al3+ was higher in populations CNPGL 136 and CNPGL 178, which also showed stability in both periods of evaluation. The second experiment was developed aiming to establish the optimum bulk size to estimate genetic diversity among Italian ryegrass populations with AFLP markers. Two populations were evaluated; from each population were characterized 30 individuals and the respective bulk samples sizes: six bulks of 5 individuals each; three bulks of 10 individuals; two bulks of 15 individuals; one bulk of 20 individuals and one bulk of 30 individuals. Six AFLP primer combinations were employed. All numbers and sizes of bulks evaluated were able to discriminate the two populations characterized. However, considering time, cost and discriminatory power, the bulk of 20 individuals is more indicated to be employed in genetic diversity analysis studies among Italian ryegrass populations. Although alleles that occur in low frequency in the populations are lost when bulks are analyzed, the evaluation of bulks, instead of individual genotypes, saves processing time of samples allows that a larger number of populations to be analyzed without identity losses.